Comparing the relationship between knowledge and support for hydraulic fracturing between residents of the United States and the United Kingdom - Stedman, Richard C.; Evensen, Derrick; O'Hara, Sarah; Humphrey, Mathew (Elsevier, 2016)
Our work examines the relationship between knowledge/familiarity with shale gas development in a comparative context. The United States (US) and United Kingdom (UK) represent very different cases of shale gas development, with development relatively mature in the US whilst, no extraction of shale gas has yet commenced in the UK. Comparing results from two national level survey efforts in 2014, we find higher levels of knowledge about the shale gas industry in the UK than in the US, as well as higher levels of support in the US (opposition levels were similar, but US respondents were much less likely than UK respondents to say that they did not know whether they supported or opposed development). With respect to the relationship between knowledge and support, increased knowledge in the UK is associated with increased support, while knowledge was unrelated to support in the US. We anchor these results within the information deficit model of science, suggesting that concentrated media and governance in the UK have played an important role in producing the demonstrated effects.